2015
DOI: 10.1007/s12035-015-9272-5
|View full text |Cite
|
Sign up to set email alerts
|

Subthreshold Concentrations of Melatonin and Galantamine Improves Pathological AD-Hallmarks in Hippocampal Organotypic Cultures

Abstract: Melatonin is a neurohormone whose levels are significantly reduced or absent in Alzheimer's disease (AD) patients. In these patients, acetylcholinesterase inhibitors (AChEI) are the major drug class used for their treatment; however, they present unwanted cholinergic side effects and have provided limited efficacy in clinic. Because combination therapy is being extensively used to treat different pathological diseases such as cancer or acquired immune deficiency syndrome, we posed this study to evaluate if mel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 49 publications
(80 reference statements)
0
16
0
Order By: Relevance
“…Extracellular deposits of Aβ peptides in Alzheimer’s are the main pathological events in AD [ 31 , 32 , 33 , 34 ]. Senile plaques or amyloid plaques mainly consist of small amyloid beta-peptides (Aβ) (up to 42 or 43 amino acids long) [ 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…Extracellular deposits of Aβ peptides in Alzheimer’s are the main pathological events in AD [ 31 , 32 , 33 , 34 ]. Senile plaques or amyloid plaques mainly consist of small amyloid beta-peptides (Aβ) (up to 42 or 43 amino acids long) [ 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…23 This observation has proposed the measurement of melatonin levels as a potential biomarker of the disease. 24 However, preclinical and clinical studies that use melatonin in AD models [25][26][27][28] or patients 25,[29][30][31][32][33] indicate that the concentrations required for a beneficial effect are much higher than the physiological concentrations. 34 For example, the neuroprotective effects of melatonin against amyloid-dependent development of AD in different in vitro and in vivo models are achieved at doses ranging from 0.1 to 50 mg and total quantities from 1 to 440 mg/kg.…”
Section: Introductionmentioning
confidence: 99%
“…The deposition of β-amyloid peptide (Aβ) in the brain is one of the pathology hallmarks of AD (Citron, 2010 ; Buendia et al, 2016 ; Sepulcre et al, 2016 ; Kreutzer et al, 2017 ). Although high concentrations of endogenous copper (Cu) (Pal et al, 2015 ; Greenough et al, 2016 ; Xu et al, 2016 ), zinc (Zn) (Kulikova et al, 2015 ; Mezentsev et al, 2016 ), and iron (Fe) (Guo et al, 2015 ; Peters et al, 2015 ; Sands et al, 2016 ; James et al, 2017 ) have been found in these amyloidal plaques, the association of those metal ions with Aβ accumulation has not been well established.…”
Section: Introductionmentioning
confidence: 99%